Asymmetric oscillation of adherent targeted ultrasound contrast agents - Zhao, Shukui (2005)
With a lipid shell containing biotin, micron-sized bubbles bound to avidin on a porous and flexible cellulose boundary were insonified by ultrasound. The oscillation of these targeted microbubbles was observed by high-speed photography and compared to the oscillation of free-floating microbubbles. Adherent microbubbles were observed to oscillate asymmetrically in the plane normal to the boundary, and nearly symmetrically in the plane parallel to the boundary, with a significantly smaller maximum expansion in each dimension for bound than free bubbles. With sufficient transmitted pressure, a jet was produced traveling toward the boundary.